2022
DOI: 10.1002/ange.202215380
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐Absorbing Chiral Open [60]Fullerenes

Abstract: Though [60]fullerene is an achiral molecular nanocarbon with I h symmetry, it could attain an inherent chirality depending upon a functionalization pattern. The conventional chiral induction of C 60 relies mainly upon a multiple addition affording a mixture of achiral and chiral isomers while their chiral function would be largely offset by the existence of pseudo-mirror plane(s). These are major obstacles to proceed further study on fullerene chirality and yet leave its understanding elusive. Herein, we showc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, dehydrative hydrogenation [17] occurred to furnish 5 in 49 % yield likely due to a single-electron reduction [2] instead of the expected orifice-enlargement reaction. The similar reductive hydrogenation took place on related substrate 6 [18] by the reaction with 4,5-dimethyl-1,2-phenylenediamine, which gave 7 in 15 % yield.…”
Section: Resultsmentioning
confidence: 73%
“…However, dehydrative hydrogenation [17] occurred to furnish 5 in 49 % yield likely due to a single-electron reduction [2] instead of the expected orifice-enlargement reaction. The similar reductive hydrogenation took place on related substrate 6 [18] by the reaction with 4,5-dimethyl-1,2-phenylenediamine, which gave 7 in 15 % yield.…”
Section: Resultsmentioning
confidence: 73%
“…[12] We also found that a consecutive addition of aromatic 1,2-diamine gives a huge orifice which allows for H 2 O, N 2 , Ar, and MeOH to be encapsulated. [13] This method could also be used for the synthesis of bilaterally π-extended C 60 derivatives, [14] as well as for the creation of π-extended C 70 derivatives. [15] Importantly, the nucleophilicity of diamines was found to change annulation and orifice cutting modes (Fig-…”
Section: Introductionmentioning
confidence: 99%
“…We chose the electromagnetic spectrum's midinfrared (MIR) portion as the laser source. MIR is non-ionizing, biologically safe, can penetrate most of the intervening media, and is absorbed by all organic compounds [17,18]. We designed a pocket-sized 2-6 µm mid-IR generating atomizer (MIRGA) and investigated the role of MIR in reducing the nicotine content and thereby detoxifying the tobacco.…”
Section: Introductionmentioning
confidence: 99%